Piperlongumine Is an NLRP3 Inhibitor With Anti-inflammatory Activity - Shi, Jie; Xia, Yang; Wang, Huihong; Yi, Zhongjie; Zhang, Ruoruo; Zhang, Xiufeng (Frontiers in Pharmacology, 2022)
Piperlongumine (PL) is an alkaloid from Piper longum L., with anti-inflammatory and anti-tumor properties. Numerous studies have focused on its anti-tumor effect. However, the underlying mechanisms of its anti-inflammation remains elusive. In this study, we have found PL is a natural inhibitor of Nod-like receptor family pyrin domain-containing-3 (NLRP3) inflammasome, an intracellular multi-protein complex that orchestrates host immune responses to infections or sterile inflammations. PL blocks NLRP3 activity by disrupting the assembly of NLRP3 inflammasome including the association between NLRP3 and NEK7 and subsequent NLRP3 oligomerization. Furthermore, PL suppressed LPS-induced endotoxemia and MSU-induced peritonitis in vivo, which are NLRP3-dependent inflammation. Thus, our study identified PL as an inhibitor of NLRP3 inflammasome, and indicated the potential application of PL in NLRP3-relevant diseases.